Pengaruh Video Edukasi Unsafe Action terhadap Tingkat Pengetahuan dan Perilaku Pekerja Weaving di PT X - Ferrall, Ajay Abdiel; Widjanarti, Maria Paskanita; Faradisha, Jihan (National Journal of Occupational Health and Safety, 2025)
The textile industry is one of the leading sectors in Indonesia, playing a crucial role in providing employment and driving economic growth. However, this industry also carries significant potential for occupational safety and health hazards, particularly due to unsafe actions. Observations at PT X revealed that workers' level of knowledge and behavior regarding unsafe actions remained low. This study was conducted with the aim of analyzing the effectiveness of an educational video intervention on unsafe actions on workers' knowledge and behavior. This quantitative research employed a quasi-experimental design using a non-equivalent control group model. The study was carried out at PT X Karanganyar from January to April 2025. The research sample consisted of 72 weaving section workers, divided into two groups: 36 workers as the experimental group and 36 as the control group. The experimental group received the educational video intervention, while the control group received no intervention. Data analysis was performed using the paired t-test and independent t-test, along with Effect Size calculation (Cohen’s d). The results indicated that the experimental group, which received the unsafe action educational video intervention, showed a significant increase in both knowledge (∆ = 2.30; p < 0.001; d =1.628) and behavior (∆ = 5.02; p < 0.001; d = 1.034). Inter-group tests revealed a significant difference in post-test knowledge (p < 0.001) with a 'very large' effect size (d = 1.705) and behavior (p < 0.001) with a 'large' effect size (d = 0.913). It can be concluded that the educational video on unsafe actions proved effective in improving the knowledge and safe behavior of weaving workers at PT X Karanganyar. Keywords: Unsafe Action, Educational Video, Safety Behavior, Occupational Safety, OHS Knowledge